Attitudes of Taxpayers, Auditors (including Chartered Accountants and Tax Practioners) towards accepting emerging trends in Tax reforms; with special reference to GST (Goods and Service Tax) based Taxation. (International Journal of Scientific Research and Management (IJSRM), 2017)
Taxes are as old as civilization. Usually Government needs enough funds to perform its traditional functions (like Maintaining law and order, Defense) and to undertake welfare and development activities. One of the major sources of such funds is Taxes, which are imposed on Nation’s people through the Tax policies. The Tax policies are subject to reforms from time to time, Recently on 1st July 2017, the Government of India (GOI) had rolled out a major reform in county’s Tax policy i.e.., Goods and Service Tax (here in after GST) and became 166th country in the world to do so. The introduction of GST was a very significant step in the field of indirect Tax reforms through amalgamating a large number of central and state Taxes into a single Tax basket. GST is a multi-stage value added Tax (VAT) levied on the supply and consumption of goods or services or both. Under GST, Taxes were collected in dual GST mechanism in which both central and state governments simultaneously levy GST on every supply of goods or services or both which takes place in a state or union territory. The scopes of Tax collection of former and later governments were increased due to widening of Tax base under GST, which pave the way for a common national market and adding transparency and effectiveness in the Tax administration After the implementation of GST, there are some hiccups in the initial days because lots of ambiguities and problems were faced by the people (including experts) about the law. Although the businesses now sailing full throttle and filing full-fledged returns, This paper aims at finding out such teething troubles faced by the different respondents like Tax payers, Chartered Accountants, Senior Tax practioners . The study was undertaken in shivamogga during the mid of July to October 2017. The responses were received through structured questionnaire and the same datas are tested through using statistical tool like SPSS. The suggestions from the respective respondents were also considered for the betterment of the study